2021
DOI: 10.12996/gmj.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antimicrobial Susceptibility Profiles of Uropathogenic Extended-Spectrum ß-Lactamase Producing Strains of Klebsiella pneumonia and Escherichia coli by the CLSI and EUCAST Methodologies

Abstract: Objective: This study aimed to compare the CLSI and EUCAST interpretations of the antimicrobial susceptibility test results of the ESBL-producing uropathogenic Escherichia coli and Klebsiella pneumonia strains. Methods: After obtaining ESBL-producing E. coli and K. pneumonia isolates from the urine specimens of the patients, Kirby-Bauer's disc diffusion method was used for conducting antimicrobial susceptibility test. The test procedures and the interpretation of the results were carried out according to both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, those isolates were described as susceptible. Although previous studies showed an acceptable level of comparability between EUCAST and CLSI (Kassim et al, 2016;Akdogan et al, 2021), one should always keep in mind that even small differences might influence the therapeutic option. We rather consider W. chitiniclastica as resistant to amikacin and tobramycin and would therefore not recommend aminoglycosides as first line treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, those isolates were described as susceptible. Although previous studies showed an acceptable level of comparability between EUCAST and CLSI (Kassim et al, 2016;Akdogan et al, 2021), one should always keep in mind that even small differences might influence the therapeutic option. We rather consider W. chitiniclastica as resistant to amikacin and tobramycin and would therefore not recommend aminoglycosides as first line treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, the ability to colonize the intestines in humans, animals, or birds is different. When selecting strains for probiotics, these and many other biological properties must be taken into account [ 4 , 5 ]. Subsequently, the approach of developing probiotics should be based on the study of many parameters, including a comprehensive assessment of the properties of microorganisms – probionts.…”
Section: Introductionmentioning
confidence: 99%